Ampliación manual de funciones del practicante transborder S.A.S. - Ibañez Acero, Arley Stuar (Universidad Antonio Nariño, 2022)
In this work, the functions performed in the company TRANSBORDER S.A.S from the import operations area are described, providing constant monitoring of loads arriving in the country in the modalities; Air, Maritime and Multimodal Transport, from different ports worldwide. Parallel to the expansion of the existing Function Manual in order to achieve an effective connection with future practitioners.